Surveillance - David Lyon (Internet Policy Review, 2022)
The concept of surveillance is vital for a digital era, especially considering that the term surveillance is several centuries old. It has been modified over time to fit new circumstances. Today, when surveillance has become part of the very infrastructure of contemporary societies, the task of understanding and updating the concept of surveillance is more important than ever. Here, the concept is defined, traced over time, elaborated upon and its current uses discussed. It is shown to be a multi-disciplinary concept, one that requires multi-faceted understanding. Today, the ubiquitous use of smart phones - a key surveillance-enabling device - and the data-analysing capacities of large organisations, public and private, means that the concept has an ongoing life and impact. It is an analytical concept but also a contested and critical one, required for understanding and engaging with our times.
Keywords: 300; Surveillance; Observation; Social sorting; Dataveillance; Big data